Factors Associated With Successful Completion of a Community-Based, Postarrest Juvenile Diversion Program and Subsequent Rearrest - NeMoyer, Amanda (Crime & delinquency, 2020)
Although diversion programs can allow arrested youth to avoid formal justice system processing, unsuccessful program completion can result in adjudication. Thus, it is important to determine whether youth successfully complete programs and identify factors linked to success. We examined records from 933 postarrest diversion program participants. Youth received a wide range of conditions during participation and the vast majority successfully completed the program, became eligible for record expungement, and avoided rearrest within 3 years. Analyses revealed significant relationships between program completion and factors related to referral charge and imposed conditions; gender and program outcome were also linked to recidivism. Results both support the use of diversion programs to limit formal juvenile justice processing and encourage further evaluation of such programs.